Mechanism of activation by CA2+ of hemolysis induced by lytic polypeptide equinatoxin II - Rudenko, S.V.; Shchetinina, E.M. (Харьковский Национальный Университет им. В.Н.Каразина, 2011)
Equinatoxin II is a cytolytic polypeptide from the sea anemone Actinia equina L. which forms pores in natural and artificial membranes. In the present study, we show that the mechanism by which Ca2+ activates toxin-induced hemolysis of human red blood cells consists of the ability of Ca2+ which enters the cell presumably through preformed toxin-induced pores and acts inside the cell to increase the rate of toxin binding to the membrane. As a result, a larger amount of pores is produced thus increasing the rate of hemolysis. In addition, the data reveal that equinatoxin II induces hemolysis of RBC interacting with a limited number of toxin-binding sites (receptors) with an upper estimate of (180 35) 103 sites per one cell. The total number of toxin-binding sites does not depend on the presence of Ca2+. These data strongly suggest that specific receptor must exist on the erythrocyte membrane to mediate the hemolytic action of this toxin.
Keywords: erythrocyte; hemolysis; divalent cations; equinatoxin II